Understanding the Market for Eco Self-Build Community Housing - Pablo Newberry (MDPI AG, 2021)
This paper evaluates the potential of eco self-build community (ESBC) housing to act as a socially and environmentally sustainable housing solution that can address the demand for self-build and community housing whilst supporting the UK’s 2050 net-zero-carbon commitment. This model of housing is being piloted through schemes such as the Water Lilies project, an upcoming ESBC scheme providing self-finish houses and custom-build flats. The research aims to gain a broad understanding of the market for ESBC housing by analysing the data from people who registered interest in a plot or home and comparing this with data from a similar survey targeted at the market for conventional self-build and custom-build housing. The key findings are that: (1) the ESBC housing market is largely open to more than one build method, but with a greater preference for purchasing a completed home and self-finish than self-build, compared to the conventional market for self-build and custom-build that is primarily interested in self-build; (2) the ESBC housing market is looking for a variety of home sizes, though predominantly 2 and 3 bedrooms, that could be provided through houses and flats, compared to the conventional market for self-build and custom-build that is mostly seeking larger houses on single plots; (3) the most important housing aspects to the ESBC housing market are ‘green lifestyle’, ‘style and construction quality’, and ‘community spirit’, which differ to the conventional self-build and custom-build market, where they are ‘construction quality’, ‘internal appearance/layout’ and ‘location’; (4) living in a sustainable home is important to the market for conventional self-build and custom-build housing and on average, they would be willing to pay 27% more for a highly sustainable home than the average UK new build. The main drivers are that people want to reduce their environmental impact and reduce their home running costs. A key overall conclusion of the study is that a distinct market exists for ESBC schemes, where the priorities of prospective homeowners differ to those from the more general self-build market. For ESBC schemes, the provision of eco-housing and a sense of community are key priorities, whereas for the more general self-build market, location and the need to tailor the house design to the owner’s unique aesthetic and lifestyle preferences tend to be the most important factors. This paper discusses the implications of these findings and identifies opportunities for scaling up the delivery of ESBC housing.